2016
DOI: 10.1016/j.ahj.2015.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic differences in atrial fibrillation symptoms, treatment patterns, and outcomes: Insights from Outcomes Registry for Better Informed Treatment for Atrial Fibrillation Registry

Abstract: Relative to white and Hispanic patients, black patients with AF had more symptoms, were less likely to receive rhythm control interventions, and had lower quality of warfarin management. Despite these differences, clinical events at 2 years were similar by race and ethnicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
87
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 22 publications
3
87
1
Order By: Relevance
“…The rate of treatment with anticoagulants in hospitalized patients with AF changes over wide range (43.0 to 88.1%)101928. Our study shows that the undertreatment of AF patients is higher than in previous reports.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…The rate of treatment with anticoagulants in hospitalized patients with AF changes over wide range (43.0 to 88.1%)101928. Our study shows that the undertreatment of AF patients is higher than in previous reports.…”
Section: Discussionmentioning
confidence: 43%
“…Several recent studies8910 have demonstrated that race- or ethnicity-dependent disparities exist in the incidence, symptoms, comorbidity burdens and outcomes of many cardiac conditions, including heart failure (HF) and AF. In addition, among patients with HF and AF, minority racial groups were shown to underutilize treatment and have disproportionately higher risks of inpatient death11.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…African-Americans are already under-treated for atrial fibrillation and are at a higher risk of stroke. That coupled with research that focuses on white populations has led to a “treatment disparity” [40, 41]. A similar problem related to lack of evidence from diverse populations has to do with the likelihood of indeterminate results in cancer genetics.…”
Section: Addressing Health Care Disparitiesmentioning
confidence: 99%
“…4 Such regional differences may be caused by many environmental factors such as geographic conditions, patients' lifestyle including their food and drink, 5 socioeconomic background, medical conditions, 6 as well as genetic factors. 7, 8 Statistics provided by the Japanese government show considerable differences in the profiles of the risk factors, medical conditions, 9 and lifestyles among various regions in Japan. 10 The annual rate of admission or hospital/clinic visits for cerebral infarctions in 2008 in 47 administrative divisions 9 are shown in Figure 1.…”
mentioning
confidence: 99%